Cost-effectiveness analysis of cadonilimab plus bevacizumab and chemotherapy for persistent, recurrent, or metastatic cervical cancer - Kaixuan Wang; Shixian Liu; Ruixue Wang; Lei Dou; Jie Gao (Frontiers in Immunology)
ObjectiveThe aim of this study is to investigate the cost-effectiveness of cadonilimab plus bevacizumab and chemotherapy in the first-line treatment for patients with persistent, recurrent, or metastatic cervical cancer from a healthcare system perspective in China.MethodsA partitioned survival model was established to estimate the total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) over a 10-year time horizon. Clinical data was sourced from the COMPASSION-16 trial; direct medical costs and utilities were obtained from a public drug bidding database and published literature. The robustness of the model was assessed via scenario, one-way and probabilistic sensitivity analyses.ResultsCadonilimab plus bevacizumab and chemotherapy yielded an additional cost of $31,654.02, with an additional QALY of 0.36, resulted in an ICER of $88,533.51/QALY compared with bevacizumab and chemotherapy. Utility values of progression-free survival (PFS), patient weight and price of cadonilimab were the most influential parameter on ICER. The probability of cadonilimab plus bevacizumab and chemotherapy being cost-effective was 0% at the WTP threshold of $38,042.49 per QALY. When the price of cadonilimab reduced by 72%, cadonilimab plus bevacizumab and chemotherapy would represent an economically viable treatment regime.ConclusionCadonilimab plus bevacizumab and chemotherapy may not be a cost-effective option as the first-line treatment in persistent, recurrent, or metastatic cervical cancer.